2015
DOI: 10.1097/meg.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long-term complications of endoscopic sphincterotomy are infections and high risk factors of bile duct and not sphincter of Oddi dysfunction

Abstract: Weakened SO function is not a decisive factor for long-term complications of EST, which were mainly influenced by biliary tract infection and high risk factors of the biliary tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…EST had been reported as an effective method for CBD stone removal by several randomized controlled trials (RCTs) [4,5], and many clinical guidelines recommended EST as a standard therapy for CBD stone removal [6]. However, the procedurerelated complications are also very common, including acute pancreatitis, severe bleeding, dysfunction of the papillary muscle, and perforation [7]. Therefore, EPBD was introduced as an alternative method [8].…”
Section: Introductionmentioning
confidence: 99%
“…EST had been reported as an effective method for CBD stone removal by several randomized controlled trials (RCTs) [4,5], and many clinical guidelines recommended EST as a standard therapy for CBD stone removal [6]. However, the procedurerelated complications are also very common, including acute pancreatitis, severe bleeding, dysfunction of the papillary muscle, and perforation [7]. Therefore, EPBD was introduced as an alternative method [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [17] reported that the basal SO pressure values in two groups of Chinese patients with choledocholithiasis were 30.88 ± 16.11 and 27.80 ± 15.88 mmHg. In a study by Yang et al [18], values of basal SO pressure, amplitude, and frequency were not reported. Our data showed mean basal SO pressure higher than 40 mmHg and indicated possible roles of SO dysfunction in patients with CBD stones.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed the involvement of SO dysfunction in patients with CBD stones and demonstrated the feasibility of EST in ERCP. Yang et al [18] reported that, instead of weakened SO function after papillotomy [15], biliary infection was a main risk factor for long-term complications after EST.…”
Section: Discussionmentioning
confidence: 99%
“…Sphincter of Oddi (SO) maintains the pressure gradient between the common bile duct (CBD) and the duodenal lumen, preventing duodenal fluid and bacterial reflux into the bile duct 7 . Yang et.al have demonstrated that after EST, SO contraction amplitude and frequency reduced markedly, and bacterial reflux into the bile duct played a role in the development of recurrent choledocholithiasis 8 . Recently, we have reported a novel method to close patulous papilla after EST: endoscopic endoclip papilloplasty (EEPP) 9 .…”
Section: Introductionmentioning
confidence: 99%